2012
DOI: 10.1007/s00128-012-0525-y
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Fuel Oil Water Accommodated Fractions on Two Marine Microalgae, Skeletonema costatum and Chlorela spp

Abstract: In this paper, the acute toxicity of four fuel oils including F120, F180, F380 and No.-20 was evaluated by exposing the marine microalgae Chlorela spp. (Chlorophyta) and Skeletonema costatum (Bacillariophyta) in the fuel oil water accommodated fractions (WAF). The bioassay showed that F180 WAF was the most toxic to both microalgae. The 96 h EC(50) value of F180 WAF for Skeletonema costatum and Chlorela spp. was 9.41 and 13.63 mg/L expressed in concentration of total petroleum hydrocarbons, respectively. WAFs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…did not show significant inhibition of growth in a WAF made of MC252 crude oil, but did in a CEWAF treatment (Garr et al 2014). Work on Skeletonema costatum has suggested this species has a high sensitivity to oil exposure (Østgaard et al 1984, Deasi et al 2010, Chao et al 2012, although some studies have found it can tolerate certain types of oil (Dunstan et al 1975, Morales-Loo andGoutx 1990 Interestingly, the two strains of Skeletonema grethae (CCMP775 and CCMP776) had contrasting physiological responses to oil and oil and dispersant. While S. grethae CCMP775 was one of the most tolerant of the phytoplankton strains tested, S. grethae CCMP776 was by far one of the most sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…did not show significant inhibition of growth in a WAF made of MC252 crude oil, but did in a CEWAF treatment (Garr et al 2014). Work on Skeletonema costatum has suggested this species has a high sensitivity to oil exposure (Østgaard et al 1984, Deasi et al 2010, Chao et al 2012, although some studies have found it can tolerate certain types of oil (Dunstan et al 1975, Morales-Loo andGoutx 1990 Interestingly, the two strains of Skeletonema grethae (CCMP775 and CCMP776) had contrasting physiological responses to oil and oil and dispersant. While S. grethae CCMP775 was one of the most tolerant of the phytoplankton strains tested, S. grethae CCMP776 was by far one of the most sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…, Chao et al. ), although some studies have found it can tolerate certain types of oil (Dunstan et al. , Morales‐Loo and Goutx ).…”
Section: Discussionmentioning
confidence: 99%
“…Coastal ecosystems account for over a third of the world’s ecosystems services, such as nitrogen fixation, phytoplankton abundance and production, bacteria growth rates, food-wed type, and the interactions between animals, plants and bacteria 18 19 20 21 22 . Diatoms are the dominant group of phytoplankton in the modern ocean, specially in well-mixed coastal upwelling regions 23 24 , accounting for approximately 40% of oceanic primary productivity and critical foundation of coastal food web 25 26 . Coastal physiological functions (including cell density (CD), protein, chlorophyll a (Chl a ), malonaldehyde (MDA), superoxide dismutase (SOD), and carbonic anhydrase (CAs)) have been used in our laboratory for the estimation of algal biomass, nutritional value, photosynthesis and respiration, lipid peroxidation, antioxidant capacity, and carbon sequestration ability, respectively.…”
mentioning
confidence: 99%
“…The indirect impact of oil pollution to plankton may result in the decrease of dissolved oxygen concentration and related degradation in water quality parameters (Harrel, 1985;Li and Boufadel, 2010;Neff and Stubblefield, 1995). Very high concentrations of crude oil may eliminate primary producers from the area, thus decreasing the food resource for heterotrophs (Chao et al, 2012;Karydis, 1982). On the other hand, species and populations respond differentially to oil pollution.…”
Section: Discussionmentioning
confidence: 98%